Polymeric sensors and actuators - Fink, Johannes Karl. (Hoboken, N.J. : Wiley-Scrivener, 2013)
'The book covers in-depth the various polymers that are used for sensors and actuators from the view of organic chemistry. The author has researched both scientific papers and patents to include all the recent discoveries and applications'--
Includes bibliographical references and index.
Print version record.
Keywords: Polymers -- Optical properties; Polymers -- Electric properties; Detectors -- Materials; Actuators -- Materials; Polymers -- Optical properties; Polymers -- Electric properties; Detectors -- Materials; Actuators -- Materials; TECHNOLOGY & ENGINEERING -- Electronics -- General; TECHNOLOGY & ENGINEERING -- Sensors; Polymers / Optical properties; Polymers / Electric properties; Detectors / Materials; Actuators / Materials; Electronic books